KONSEP HUTAN WAKAF DALAM PELESTARIAN HUTAN DAN PENCAPAIAN SDGs: PELUANG DAN TANTANGAN PADA PROVINSI KONSERVASI PAPUA BARAT - Muhammad Yahya Saifuddin; Diah Aghsari (Ekonomi Islam, 2022)
This paper examines the opportunities and challenges of the Waqf Forest Concept in Forest Conservation and the Achievement of SDGs in the Conservation Province of West Papua. The process of collecting information using the Literature Study method. The concept of waqf forest considers the increasing threat of environmental crises, mainly due to uncontrolled deforestation. Efforts to protect ecosystem use sustainably are in line with the idea of Sustainable Development Goals (SDGs). Furthermore, West Papua Province is a conservation province moving towards more sustainable development. The opportunity for the concept of waqf forest in the conservation province of West Papua is very suitable for preserving forests because of its characteristics that are in line with environmental sustainability, which positions sustainable development and conservation in every activity and economic growth in West Papua Province. Then the challenges related to waqf literacy, the collaboration between institutions, not optimal waqf institutions and human resources, and the readiness of the waqf forest management budget. Keywords: Waqf Forest, Forest Preservation, SDGs, Conservation, West Papua.